2019
DOI: 10.1101/533042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reallocation to lateral and early-emerging axial roots allows maize (Zea mays L.) with reduced nodal root number to more efficiently forage for nitrate

Abstract: Short title:Reduced nodal rooting leads to more foraging roots Summary:Reallocating root biomass from nodal roots to lateral and early-emerging axial roots allows grasses to capture more nitrogen under limiting conditions, including by increasing foraging at depth. ABSTRACTPrevious simulations indicated reduced nodal root number (NRN) was promising for maize (Zea mays L.) breeding, and were partially confirmed using variation in NRN among inbreds. However, the exact mechanism was unknown, therefore manipulativ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In contrast, N (as nitrate) is relatively mobile in the soil compared to P and moves down the soil strata with irrigation and precipitation events. Fewer crown roots in maize, for example, can potentially improve N acquisition by exploring deep soil strata, a key root system response (Saengwilai et al 2014;Guo and York 2019). Therefore, the coordinated uptake and utilization of both N and P are essential in relation to optimal plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, N (as nitrate) is relatively mobile in the soil compared to P and moves down the soil strata with irrigation and precipitation events. Fewer crown roots in maize, for example, can potentially improve N acquisition by exploring deep soil strata, a key root system response (Saengwilai et al 2014;Guo and York 2019). Therefore, the coordinated uptake and utilization of both N and P are essential in relation to optimal plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…Given that nutrient foraging by roots is an active process (Zhang et al 2019), it is very likely that plant biomass allocation and root system responses will be driven by the nutrient which is limiting plant growth the most (Poorter et al 2012). It has previously been shown for many crops how eco-physiological (Gastal and Lemaire, 2002), morphological (Fransen et al 1998), architectural (Williamson et al 2001; Lopez-Bucio et al 2003; Postma and Lynch, 2012; Lynch, 2013; Guo and York, 2019), and anatomical (Wahl et al 2001; Postma and Lynch, 2011) root traits respond to nitrogen (N) and phosphorus (P) availability in soil. For instance, Wang et al (2015) showed contrasting root morphological and physiological trait responses of canola, barley, and potato in relation to low P availability.…”
Section: Introductionmentioning
confidence: 99%